KAJIAN KONSEPTUAL SILABEL RITME GANDANG MINANGKABAU - Fallen, Aryuda Fakhleri; Sukmayadi, Yudi; Narawati, Tati (Paradigma: Jurnal Kajian Budaya, 2024)
This article tryes to initiate the concept of Minangkabau rhythm syllables, which is a method in music learning related to audiation in rhythm learning, the urgency in this study explores the basic elements of the audiation system that can be applied to music learning related to rhythm syllables based on local approaches, taking into account previous concepts that have been popular in recent schools. In West Sumatra, the concepts of syllable rhythm such as Zoltan Kodaly, Kannokol, American Style Syllables, and Edwin Gordon are not so popular, but environments such as schools and art studios have their own ways of approaching learning music related to pronouncing sounds, so that in this study it is addressed as an interesting and crucial thing to study and formulate further into formulations. The method used in this research uses a qualitative paradigm with a literature review approach. Where the concept of previous rhythmic syllables is used as a reference in analyzing, bringing up findings, and juxtaposing the findings with the initiated Minangkabau rhythmic syllable formula, so that the Minangkabau rhythmic syllables can be generalized and adapted, but still referring to the habits of the local community material. Based on the results of the analysis, like Gordon’s concept, it is found that syllables or audiation appear after the formation of rhythms, patterns and sound colo.